Reaching for a new deal : ambitious governance, economic meltdown, and polarized politics in Obama's first two years - Skocpol, Theda; Jacobs, Lawrence R. (Russell Sage Foundation, 2011)
Reaching for a New Deal analyzes both the ambitious domestic policy of Obama's first two years and the consequent political backlash--up to and including the 2010 midterm elections. --from publisher description.